2000
DOI: 10.1177/089686080002000412
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Peritoneal Dialysis is a Risk Factor of Sclerosing Encapsulating Peritonitis for Children

Abstract: Objective Sclerosing encapsulating peritonitis (SEP) is a clinical syndrome with a high mortality rate and is a serious complication of peritoneal dialysis (PD). Peritoneal sclerosis (PS) is a histological diagnosis. PS is usually observed in the peritoneal specimens of patients with SEP. Avoiding SEP is considered to be extremely important for pediatric patients who may require long-term PD. In this study, the characteristics of patients with PS were investigated to determine when to perform peritoneal biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…The outer portion of the peritoneum is usually replaced by hyalinized collagen. 4 All of these histological findings were detected in the first patient in the present study. Kawaguchi et al . proposed that a diagnosis of EPS was based on clinical suspicion and confirmed with radiological findings.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The outer portion of the peritoneum is usually replaced by hyalinized collagen. 4 All of these histological findings were detected in the first patient in the present study. Kawaguchi et al . proposed that a diagnosis of EPS was based on clinical suspicion and confirmed with radiological findings.…”
Section: Discussionsupporting
confidence: 66%
“…3,5 It was found that the risk of EPS increased with the duration of dialysis. 1,3,4 Kawanishi et al . reported that there were no cases of EPS in patients with a PD duration shorter than 3 years, and its incidence increased especially after 8 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bowels become cocooned in a restrictive fibrocollagenous sheath and may become obstructed. EPS can be associated with high mortality, 60 but in children this is rare. The child is usually unwell, with abdominal symptoms and signs of bowel obstruction.…”
Section: Abdominal Wall Herniasmentioning
confidence: 99%